TGFB1/CXCL5 axis regulation by LCN2 overexpression: a promising strategy to inhibit colorectal cancer metastasis and enhance prognosis - Song, Xiaotian; Xu, Shuai; Song, Dan; Wang, Juan; Bai, Bin; An, Yanxin; Yang, Bin; Wang, Shiqi; Zhao, Qingchuan; Yu, Pengfei (Frontiers in Immunology, 2025)
BackgroundDistant metastasis remains a major reason for the high recurrence and mortality of colorectal cancer (CRC). However, the underlying molecular mechanisms driving metastasis in CRC remain poorly understood. In this study, we investigated the mechanisms underlying the inhibitory effects of lipocalin-2 (LCN2) on CRC metastasis.MethodsWe assessed the expression and clinical significance of LCN2 in human CRC specimens and CRC cell lines using, immunohistochemistry, and western blot analyses. We evaluated the migratory and invasive capabilities of CRC cells influenced by LCN2 using in vitro transwell assays and in vivo lung metastatic models. RNA sequencing and proteome analysis were employed to identify potential downstream targets of LCN2. Rescue experiments were conducted to further elucidate the potential mechanisms of LCN2 and its downstream effectors in CRC.ResultsLCN2 exhibited high expression levels in human CRC tissues and an inverse correlation with N classification, advanced AJCC stages, and shorter overall survival. LCN2 expression independently predicted a more favorable outcome for CRC patients. Upregulation of LCN2 effectively suppressed CRC cell metastasis both in vitro and in vivo. Mechanistically, Transforming growth factor beta 1 (TGFB1) and C-X-C motif chemokine ligand 5 (CXCL5) were identified as downstream effectors of LCN2, with LCN2 inhibiting CRC metastasis through repression of the TGFB1/CXCL5 axis. Furthermore, either TGF-βR1 inhibitor SB431542 or CXCR2 antagonist SB225002 treatment moderately decreased the migratory and invasive capabilities of DLD-1-LV-shLCN2 cells, whereas the combination treatment of the two agents dramatically decreased the migratory and invasive capabilities of DLD-1-LV-shLCN2 cells.ConclusionsThis study underscores LCN2 as an independent protective factor and prognostic biomarker for CRC patients. Combined treatment with the SB431542 and the SB225002 significantly attenuated LCN2-related CRC metastasis. Targeting the LCN2/TGFB1/CXCL5 axis emerges as a promising therapeutic strategy for managing LCN2-related metastatic CRC.